Behavioural factors in B2B price negotiation: a case from air cargo market - Salihoğlu, Salih Kâmil (İstanbul Bilgi Üniversitesi, 2023)
ABSTRACT: Behavioral pricing research in B2B markets is still in its infancy, albeit it has shown critical improvements in the last decades. Moreover, finding any examples in which behavioral pricing is studied in logistics is almost impossible. To the author, such a study examining the air cargo sector has not yet been done. In this study, behavioral effects on price negotiations in B2B sectors were observed, taking pricing negotiations in the air cargo industry as an example. The study’s primary purpose is to show the impact of behavioral concepts, namely aspiration price, reservation price, initial price offer, and reference price on the B2B price negotiation process and outcome. On the other hand, the effects of anchoring bias on the determination of reference prices and the formation of the negotiation result are also observed. In addition, it is investigated whether there is difference in explanation of price negotiation between student and employee samples. This study includes the results of 258 price negotiation experiments in which 516 people participated in the period of May-November 2022. The results of the experiments showed that the buyer has a more influential position on the price negotiation outcome than the seller. In addition, the most critical reference prices are the buyer's aspiration price and initial price offer. Apart from this, the anchor price affects both the seller and the buyer to determine the reservation prices before the negotiation. Finally, the regression models explaining the price negotiations of student and employee subjects are statistically significantly different. In other words, there are significant difference between student and employee samples which make it necessary to be taken into deep consideration while using student samples in business related studies. As the most critical findings of the study and its contribution to the literature, it can be said that the buyer has a stronger influence than the seller in B2B price negotiations and that student subjects have different results than employee subjects.

ÖZET: Son onlu yıllarda önemli gelişmeler göstermiş olsa da B2B bağlamında davranışsal fiyatlandırma araştırmaları halen daha emekleme aşamasındadırlar. Ayrıca lojistik alanında davranışsal fiyatlandırmanın incelendiği herhangi bir örnek bulmak neredeyse imkansızdır. Yazarın bildiği kadarıyla, hava kargo sektörünü inceleyen böyle bir çalışma ise henüz yapılmamıştır. Bu çalışmada, hava kargo sektörü fiyat müzakeresi örnek alınarak B2B sektörlerinde fiyat görüşmelerinde davranışsal etkiler gözlemlenmiştir. Çalışmanın temel amacı; hedef fiyat, son fiyat, açılış teklifi ve referans fiyat ismindeki davranışsal kavramların B2B fiyat müzakereleri üzerinde etkilerini göstermektir. Öte yandan, çıpa yanlılığının referans fiyatların belirlenmesinde ve müzakere sonucunun oluşmasında da etkileri araştırılmıştır. Ayrıca öğrenci ve çalışan örneklemleri arasında fiyat pazarlığının açıklanmasında farklılık olup olmadığı araştırılmıştır. Bu çalışma, 2022 yılı Mayıs-Kasım döneminde 516 kişinin katıldığı 258 fiyat pazarlığı simülasyonunun sonuçlarını içermektedir. Deneylerin sonuçları, alıcının fiyat müzakere sonucu üzerinde satıcıdan daha etkili bir konuma sahip olduğunu göstermiştir. Ayrıca en kritik referans fiyatları, alıcının hedef fiyatı ve açılış teklifidir. Bunun dışında çıpa fiyatı hem satıcıyı hem de alıcıyı pazarlık öncesi son fiyatlarının belirlenmesinde etkiler. Son olarak, öğrenci ve çalışan deneklerin fiyat görüşmelerini açıklayan regresyon modelleri istatistiksel olarak anlamlı bir şekilde farklıdır. Diğer bir deyişle, öğrenci örneklemi ile çalışan örneklemi arasında anlamlı fark vardır ve bu da işle ilgili çalışmalarda öğrenci örneklemi kullanılanımın dikkatle ele alınmasını gerekli kılar. Çalışmanın en kritik bulgusu ve literatüre katkısı olarak B2B fiyat görüşmelerinde alıcının satıcıya göre daha güçlü bir etkiye sahip olduğu ve öğrenci deneklerin çalışan deneklerden farklı sonuçlar verdiği söylenebilir.
B2B fiyat müzakerelerinde davranışsal etmenler: hava kargo piyasasından bir örnek
Keywords: Davranışsal Fiyatlama; B2B Piyasalar; Hava Kargo Fiyatlama; Fiyat Müzakereleri; Davranışsal Deney; Behavioural Pricing; B2B Markets; Air Cargo Pricing; Price Negotiations; Behavioural Experiment